2010
DOI: 10.1111/j.1399-0004.2010.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Nature and nurture: the complex genetics of myopia and refractive error

Abstract: The refractive errors, myopia and hyperopia, are optical defects of the visual system that can cause blurred vision. Uncorrected refractive errors are the most common causes of visual impairment worldwide. It is estimated that 2.5 billion people will be affected by myopia alone with in the next decade. Experimental, epidemiological and clinical research has shown that refractive development is influenced by both environmental and genetic factors. Animal models have demonstrated that eye growth and refractive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
230
0
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(247 citation statements)
references
References 173 publications
(219 reference statements)
2
230
0
15
Order By: Relevance
“…A number of previous studies have extensively examined the impact of genetic effects on myopia in humans (44)(45)(46). The analysis of genes involved in the scleral extracellular matrix (ECM) is a common feature of studies on syndromic high myopia (47).…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have extensively examined the impact of genetic effects on myopia in humans (44)(45)(46). The analysis of genes involved in the scleral extracellular matrix (ECM) is a common feature of studies on syndromic high myopia (47).…”
Section: Discussionmentioning
confidence: 99%
“…Myopia often exhibits apparent familial aggregation (10)(11)(12), and the number of myopic parents is significantly correlated with myopic onset and progression in children (13). Twin studies and population-based epidemiological investigations show that genetic factors significantly contribute to the development of myopia (6,14,15), particularly HM (5). Genomewide association studies (GWAS) and subsequent metaanalyses have identified dozens of loci and genes that are associated with general myopia or HM (16,17).…”
mentioning
confidence: 99%
“…This group includes genes that encode matrix metalloproteinases (MMP1, MMP2, MMP3, and MMP9), growth factors and growth factor receptors (HGF, TGFB1, TGFB2, and MET), collagens (COL1A1 and COL2A1), and proteoglycans (LUM) (see Wojciechowski 80 for summary).…”
Section: Refractive Errormentioning
confidence: 99%